Quantitative indicators for the organotrophic bacteria in the pelagial and littoral water of Lake Ohrid - Novevska, Vera; Lokoska, Lenče (Macedonian Journal of Ecology and Environment, 1997)
In this paper are presented quantitative data of the organotrophic bacteria (saprophitic and oligotrophic) in the pelagial and littoral water of Lake Ohrid during the period May-September 1997.